2009
DOI: 10.1083/jcb.200906084
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of OPA1 processing and mitochondrial fusion by m-AAA protease isoenzymes and OMA1

Abstract: m-AAA proteases cleave OPA1 to ensure a balance of long and short OPA1 isoforms, whereas cleavage by OMA1 causes an accumulation of the short OPA1 variants. (See also companion paper from Head et al. in this issue.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
581
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(599 citation statements)
references
References 39 publications
(95 reference statements)
17
581
1
Order By: Relevance
“…4). This was recently observed for the dynamin-like GTPase OPA1 in the IM, in which addition of the protease inhibitor MG132 stabilized the precursor forms of newly synthesized OPA1 resulting in the accumulation of mature OPA1 within mitochondria (Ehses et al 2009). Proteins that reside in the OM are accessible to UPS machinery and increasing evidence suggests that certain mitochondrial OM proteins are ubiquitinated and subjected to turnover via the UPS pathway (Fig.…”
Section: Turnover Of Mitochondrial Om Proteins-exploiting the Upsmentioning
confidence: 95%
See 3 more Smart Citations
“…4). This was recently observed for the dynamin-like GTPase OPA1 in the IM, in which addition of the protease inhibitor MG132 stabilized the precursor forms of newly synthesized OPA1 resulting in the accumulation of mature OPA1 within mitochondria (Ehses et al 2009). Proteins that reside in the OM are accessible to UPS machinery and increasing evidence suggests that certain mitochondrial OM proteins are ubiquitinated and subjected to turnover via the UPS pathway (Fig.…”
Section: Turnover Of Mitochondrial Om Proteins-exploiting the Upsmentioning
confidence: 95%
“…The mammalian homolog of Pcp1, PARL, has been linked to the release of short OPA1 isoforms from mitochondria during apoptosis and suggested to play a role in OPA1 processing (Cipolat et al 2006). However, studies in cell lines lacking PARL, revealed that it is dispensable for OPA1 cleavage (Cipolat et al 2006;Duvezin-Caubet et al 2007;Ehses et al 2009). Rather, the i-AAA protease Yme1 has been implicated in generation of at least one short form of OPA1 by constitutive cleavage at the processing site Following lateral release into the lipid bilayer, OPA1 is subjected to constitutive processing at site 1 (S1) and by Yme1 at site 2 (S2), generating long and short forms of the protein (L and S OPA1) that ensure mitochondrial fusion.…”
Section: Processing Of the Dynamin-like Gtpase Opa1mentioning
confidence: 99%
See 2 more Smart Citations
“…12 The activity of OPA1 is regulated by proteolytic cleavage. Paraplegin, YME1L and OMA1 proteases have all been shown to cleave OPA1, [13][14][15][16][17] thus implicating them in the regulation of mitophagy. The mitochondrial rhomboid protease presenilin-associated rhomboid-like (PARL) is also implicated in regulating mitophagy by cleaving PINK1, 18,19 a kinase required for mitophagy.…”
mentioning
confidence: 99%